Pengelolaan Keuangan Desa: Menilik Peran Perangkat Desa dalam Peraturan Menteri Dalam Negeri (Permendagri) Nomor 20 Tahun 2018 - T. Fahrul Gafar; Suryaningsih Suryaningsih; Zamhasari Zamhasari; Yahya Krisnawansyah (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
After the revision of Permendagri Number 113 of 2014 to Permendagri Number 20 of 2018 concerning Village Financial Management, there has been a change in the role of village officials in managing village finances. The purpose of this paper is to look at the new role of village officials in managing village finances based on Permendagri Number 20 of 2018. The author uses the literary studies method. The findings from this study are that village financial management includes: planning, implementation, administration, reporting, and accountability. The role of village officials in the planning stage is compiling the RKP Desa and APBDesa documents, in the implementation stage compiling DPA, DPPA, DPAL, and self-supporting books, in the administration stage compiling cash books, bank ledgers and tax auxiliary books, in the reporting stage compiling reports realization of activities, and at the accountability stage prepare budget realization reports (LRA), notes on financial reports (CaLK), reports on the realization of activity implementation, and sectoral activity reports.